Pour un changement de paradigme dans la politique d’attractivité résidentielle en Région de Bruxelles-Capitale - Hannah Berns; Emmanuelle Lenel; Christine Schaut; Gilles Van Hamme (Brussels Studies, 2022)
This article looks at one of the central issues of the Brussels-Capital Region since it was formed in 1989: the migration of the middle classes to the outskirts. After 30 years, it is clear that policies aimed at keeping average households in BCR have failed. We show that this failure is the result of an error with respect to the target (average households with children) as well as the means (the emphasis on ownership), denying the reality of the city as a place of transition: on the one hand, average households with children represent only a moderate fraction of departures and are particularly difficult to retain in a dense urban environment; on the other hand, access to ownership hardly seems to be an effective means of anchoring the population. We therefore propose a paradigm shift: acknowledge that the city is a place of transition and determine which groups BCR could seek to attract as well as the means to achieve this.